193 Epidemiological trend of amyloidosis and its association with cardiovascular conditions: a single-center report. (8th December 2021) - Licchelli, Luca; De Michieli, Laura; Sinigiani, Giulio; Berno, Tamara; Previato, Lorenzo; Iliceto, Sabino; Cipriani, Alberto
Abstract: Aims: Despite improved awareness and advances in cardiac imaging, cardiac amyloidosis (CA) is a substantially underdiagnosed disease. ATTRwt amyloidosis may be responsible for as many as 30% of HF with preserved ejection fraction in patients >75 years old. Contemporary estimates of its epidemiology in Italy are poorly provided. The aim of this study is to retrospectively analyse yearly inpatient claims consistent with amyloidosis in a single centre of Veneto region (Azienda Ospedaliera—Università di Padova). Methods: Inpatient claims were counted in the series in each year if they had at least 1 principal or secondary International Classification of Diseases, Ninth revision—clinical modification (ICD-9, CM) code for amyloidosis (27730-27739), from January 2009 to February 2021. Primary outcome was to clarify if an increase in claims went hand in hand with novel and wider awareness of the disease. Secondary outcome was to identify major comorbidities determining or accompanying acute conditions leading to hospitalization. Results: During the study period, there was a total of 328 claims containing ICD9-CM code for amyloidosis; 139 of them (42%) registered before 2015, 189 (58%) after 2015. Mean number of hospitalizations increased during time, starting from 20 claims per year between 2009 and 2015, to 36.8 from 2015 to 2020 (excluded current year). Considering main discharge diagnosis, 84 (25.6%) was related to cardiological condition, of them 56 (66%) was about acute or acute on chronic heart failure, 9 (10.7%) to arrhythmias, both brady- and tachyarrhythmia, 6 (7.1%) to coronary disease, 4 (4.8%) to aortic stenosis. The other most frequent discharge diagnoses, 36 (10.9%) were due to neurological condition, mostly neurovascular disease, 26 (7.9%) were due to haematological disease, mostly multiple myeloma, 14 (4.2%) were about nephrological condition, mostly related to advanced or pre-dialysis renal disease. Regarding related discharge diagnoses, the most frequent were cardiological conditions, appearing in 205 (62.5%) claims. 128 (62.4%) of them were due to acute or chronic heart failure, 10 (4.1%) to brady-tachyarrhythmias, 9 (4.4%) to ischaemic heart disease, and 6 (2.9%) to aortic valve disease. About other associated conditions reported in ICD9-CM codes used 84 (25.6%) were related to haematological diseases, 68 (20.7%) to neurological disease, 52 (15.8%) to renal disease, 23 (7%) to gastroenterological diagnoses (mostly GI bleeding). Conclusions: Over the last years, there have been a substantial increase in amyloidosis diagnosis in our centre. This appears to go hand in hand with an increase in clinicians' CA awareness, as confirmed by the fact that main discharge diagnosis is related to cardiac condition, and more specifically heart failure. Heart is again the most important comorbidity in patients hospitalized for other conditions, mostly related to nephrological, neurological, haematological affections confirming its role as main prognostic determinant in a complex disease, and the necessity to search for it, find it and quickly cure it.